Oxidative and Anti-Oxidative Stress Markers in Chronic Glaucoma: A Systematic Review and Meta-Analysis. - Cédric Benoist d'Azy; Bruno Pereira; Frédéric Chiambaretta; Frédéric Dutheil (PLoS ONE, 2016)
Chronic glaucoma is a multifactorial disease among which oxidative stress may play a major pathophysiological role. We conducted a systematic review and meta-analysis to evaluate the levels of oxidative and antioxidative stress markers in chronic glaucoma compared with a control group. The PubMed, Cochrane Library, Embase and Science Direct databases were searched for studies reporting oxidative and antioxidative stress markers in chronic glaucoma and in healthy controls using the following keywords: "oxidative stress" or "oxidant stress" or "nitrative stress" or "oxidative damage" or "nitrative damage" or "antioxidative stress" or "antioxidant stress" or "antinitrative stress" and "glaucoma". We stratified our meta-analysis on the type of biomarkers, the type of glaucoma, and the origin of the sample (serum or aqueous humor). We included 22 case-control studies with a total of 2913 patients: 1614 with glaucoma and 1319 healthy controls. We included 12 studies in the meta-analysis on oxidative stress markers and 19 on antioxidative stress markers. We demonstrated an overall increase in oxidative stress markers in glaucoma (effect size = 1.64; 95%CI 1.20-2.09), ranging from an effect size of 1.29 in serum (95%CI 0.84-1.74) to 2.62 in aqueous humor (95%CI 1.60-3.65). Despite a decrease in antioxidative stress marker in serum (effect size = -0.41; 95%CI -0.72 to -0.11), some increased in aqueous humor (superoxide dismutase, effect size = 3.53; 95%CI 1.20-5.85 and glutathione peroxidase, effect size = 6.60; 95%CI 3.88-9.31). The differences in the serum levels of oxidative stress markers between glaucoma patients and controls were significantly higher in primary open angle glaucoma vs primary angle closed glaucoma (effect size = 12.7; 95%CI 8.78-16.6, P < 0.001), and higher in pseudo-exfoliative glaucoma vs primary angle closed glaucoma (effect size = 12.2; 95%CI 8.96-15.5, P < 0.001). In conclusion, oxidative stress increased in glaucoma, both in serum and aqueous humor. Malonyldialdehyde seemed the best biomarkers of oxidative stress in serum. The increase of some antioxidant markers could be a protective response of the eye against oxidative stress.